(untitled) (Research, Society and Development, 2021)
The experience of those who have an autoimmune disease such as psoriasis affects people’s physical appearance and psychosocial status. It can bring significant harm to these people’s lives. The study aimed to analyze the experience of chronic illness from psoriasis lived and documented on the YouTube platform. It is documental, qualitative research. The collected data was through the selection of videos from the YouTube platform with autobiographical narratives about psoriasis. Data collection took place in February and March 2021, retrieving six videos available on YouTube. The transcripts of the videos were subjected to thematic-reflective analysis and later discussed based on the scientific literature on psoriasis, especially in the field of mental health. Was produced two main themes: (1) psoriasis discovery and diagnosis; (2) feelings, prejudice towards psoriasis, and how it affects the quality of life of people affected by the disease. The YouTubers’ narratives revealed that psoriasis promoted negative feelings, with emotional, physical, and social repercussions. The reports reinforced the importance of an accurate and early diagnosis for better management of the psychosocial effects of this condition. Investigating the role of this social network in the deconstruction of stigmas associated with psoriasis is a recommendation for further studies.